Microstructure Characterization, Mechanical and Wear Behavior of Silicon Carbide and Neem Leaf Powder Reinforced AL7075 Alloy hybrid MMC’s. (Fracture and Structural Integrity, 2023)
The demanding material quality criteria in the automotive and aerospace industries have recently had an impact on the development of lightweight aluminium alloys. The choice and application of metal-matrix composites as structural materials in this context are known to offer a variety of benefits. These benefits include the ability to combine high elastic modulus, toughness, and impact resistance; minimum sensitivity to change in temperature or thermal shock; durability of the surface is good; moisture absorption leads to the potential issue while minimum exposure which leads to environmental degradation; and improved fabricability with conventional metalworking equipment. Aluminium metal matrix composites (AMMCs) are a potential material for advanced structural, aviation, aerospace, marine, and defence applications, as well as for the automotive sector and other related fields, due to their outstanding combination of qualities. The stir casting procedure is used to create an aluminium metal matrix composite (AMMC), which is the most efficient way to do so. In this study, the aluminium alloy 7075 is strengthened using neem leaf powder and SiC. The Vickers hardness examination method is used to govern the hardness of hybrid composites. Eventually, the mechanical and tribological properties of the composites were assessed, and their relationship to the composites' matching microstructure and wear was addressed.
Keywords: Al7075; SiC; Neem Leaf Powder; Stir Casting; Wear; Metal Matrix Composites